Treatment of benign lesions of the proximal femur in young pediatric patients using adult 3.5 mm proximal humerus locking plates - Zhao, Zhiqiang; Liu, Xin; Xie, Xianbiao; Zou, Changye; Yin, Junqiang; Li, Haomiao; Shen, Jingnan (Frontiers in Oncology, 2025)
This study aimed to assess the efficacy of using adult 3.5 mm proximal humerus locking plates (PHLPs) for treating benign proximal femur lesions in skeletally immature pediatric patients. Between 2011 and 2021, 22 skeletally immature pediatric patients were treated with adult 3.5 mm PHLPs for benign lesions of the proximal femur. During this period, indications for the procedure included lesions involving bone cyst (BC), aneurysmal bone cyst (ABC), and fibrous dysplasia (FD) of the proximal femur, resulting in impending or actual pathologic fractures. The mean follow-up time for the entire group of patients (n=22) was 57 months (range, 27–118 months). A visual analog scale (VAS) scoring system was used for patients with pathological fractures to assess postoperative pain relief. Functional outcomes were evaluated using the Musculoskeletal Tumor Society (MSTS) lower extremity scoring system. Postoperatively, the mean total MSTS score (measured at the most recent follow-up) was 29.41 (95% CI, 29.11 to 29.70) for the entire group of patients. The mean pain relief for patients with actual pathological fractures assessed by VAS was 4.88 (95% CI, 4,30 to 5.45). One patient with ABC and two patients with FD experienced recurrences, necessitating a second surgery at 22, 10, and 15 months post-initial surgery, respectively. Following the second surgery, the locking plates in the patients with ABC and one FD case were removed 30 and 12 months after the initial surgery. The third FD patient, who did not have a pathological fracture, retained the locking plate as of the latest follow-up. Only one patient had delayed wound healing after the initial surgery, and the others had no other complications. 18 patients had their locking plates removed at a mean time of 23 months (95% CI, 18 to 28). In conclusion, treatment of benign lesions of the proximal femur in young pediatric patients with adult 3.5 mm PHLPs provides good functional outcomes and radiological results.